Assembly type submerged plant plantation apparatus - SUN XINGFU; SUN TONG; LI GUO; HE QIANG; AI HAINAN; LI LI; GU LI (2016)
The invention discloses an assembly submerged plant plantation apparatus and belongs to the field of water ecological restoration processing. The plantation apparatus comprises a plantation body. The plantation body is divided into an internal layer and an external layer, wherein a cross section of the internal layer is round; a cross section of the external layer is regular hexagonal; the distance between the center of each side of the regular hexagon and the intern layer is 10 to 15cm; a plurality of submerged plant plantation grooves are evenly formed in the internal layer of the plantation body; each submerged plant plantation groove passes through the internal layer from top to bottom; the bottom of the plantation groove is provided with a degradable plant fiber filter net; a banding belt hole is respectively formed on two sides of each corner of the external layer; and light flotage capable of floating on the water surface is arranged in one of the band belt hole via a fine rope. The submerged plant pla